Pembiayaan Daerah dalam Keuangan Negara: Tinjauan atas Pengaruh dan Mekanismenya terhadap Ekonomi Daerah - Nursuhayla, Risma; M, Melati; Putri, Viola Augustia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines regional financing and its impact on economic development through a literature review of 10 relevant journals. Regional financing plays a crucial role in supporting infrastructure development, regional economic empowerment, and fiscal stability. Through the review of various sources, it was found that regional financing, which includes general allocation funds, regional bonds, and ultra-micro financing, has a significant impact on economic growth and community welfare. Furthermore, transparency, accountability, and the use of technology in managing regional budgets have proven to enhance the effectiveness of regional financing. The study’s findings indicate that well-managed regional financing can accelerate the achievement of regional development goals and strengthen the local economy. Therefore, regional financing must be carefully